Rethinking commercial complex , Shapla Chottor, Motijheel: a vision to create a flagship project that would demonstrate the economic and social value of building high density structures at major transport nodes - Hoque, Anika (BRAC University, 2014)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Architecture in Architecture, 2014.